THE PURPOSE OF THE USE CLASSROOM LANGUAGE - Hapsari Oka, Ida Ayu Puspitha Pradnya; Artini, Luh Putu (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Currently, there are still many who cannot use English. The results of previous studies also stated that the cause of students not being able to speak English was because students thought learning English was complicated. English in everyday life is still rare, so students have difficulty understanding English. This study aimed to analyze the classroom language used by the English teacher and to analyze the purpose of using the classroom language during the learning process. This study uses a case study using descriptive qualitative research. The object of this research is 1 English teacher. Data were collected by observation and interviews. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The results of this study indicate that first, the English teacher uses language based on the situations encountered during class. Second, the teacher chooses the class language based on the teacher's goals from the students during the learning process. This study categorizes three purposes of classroom language use: motivating, instructing, and guiding. Each plan has a different frequency in one meeting. The analysis results are supported by the teacher's statements obtained through interviews regarding how the situation requires certain types of language objectives. The use of classroom language has different purposes according to the current situation in the learning range.